For us, what music? : the life and poetry of Donald Justice - Harp, Jerry (University of Iowa Press, 2010)
When Donald Justice wrote in "On a Picture by Burchfield" that & "art keeps long hours," he might have been describing his own life. Although he early on struggled to find a balance between his life and art, the latter became a way of experiencing his life more deeply. He found meaning in human experience by applying traditional religious language to his artistic vocation. Central to his work was the translation of the language of devotion to a learned American vernacular. Art not only provided him with a wealth of intrinsically worthwhile experiences but also grante.